PENGARUH PEMBERIAN JUS BONGGOL NANAS (ANANAS COMOSUS (L.) MERR) TERHADAP KADAR GLUKOSA TIKUS PUTIH JANTAN (RATTUS NORVEGICUS) YANG DIINDUKSI ALOKSAN - Santi Widiasari; Muhammad Habib Miftah Al-basyari; Eva Oktariani; Riski Dwi Utami; Wahyu Ramadhan (LPPM Universitas Abdurrab, 2025)
Diabetes Mellitus (DM) is a chronic metabolic disease characterized by increased blood glucose levels, which over time can cause damage to the heart, blood vessels, eyes, kidneys and nerves. Some plants that are known to lower blood glucose levels are pineapple, which contains flavonoids in the pineapple tuber. Flavonoid compounds are known to have strong antioxidant activity. By giving pineapple tuber juice, it is hoped that it can reduce blood glucose levels, one of which is by regenerating damaged pancreatic beta cells and stimulating pancreatic beta cells to produce insulin. The aim of this study was to determine the effect of giving pineapple tuber (Ananas comosus (L.) Merr) juice on the glucose levels of male white rats (Rattus norvegicus) induced by alloxan. This research method is experimental research that uses a